Šport in spol v antiki: nejasna razmerja - Slapšak, Svetlana (Monitor ISH, 2006)
The aim of the paper is to establish a critical distance between the modern notions of sport and gender, and gender relations as we read them in the Ancient Greek culture. The presence or absence of women in sports does not crucially exemplify any position of women which we have not realised before, but it enlarges the imaginary of gender relations inside the religious sphere, which is certainly the most complicated of all socio-cultural structures when it comes to Ancient gender/identity constructs.
Keywords: antična antropologija; antična kultura; sport; šport; odnosi med spoloma; woman; ženske; razlike med spoloma